Alcohol - World Bank (Washington, DC, 2012)
Alcohol abuse is one of the leading causes of death and disability worldwide. Alcohol abuse is responsible for 4 percent of global deaths and disability, nearly as much as tobacco and five times the burden of illicit drugs (WHO). In developing countries with low mortality, alcohol is the leading risk factor for males, causing 9.8 percent of years lost to death and disability. Alcohol abuse contributes to a wide range of social and health problems, including depression, injuries, cancer, cirrhosis, dependence, family disruption, and loss of work productivity. Health and social problems from drinking often affect others besides the drinker. While men do the bulk of the drinking worldwide, women disproportionately suffer the consequences, including alcohol related domestic violence and reduced family budgets. Heavy alcohol use takes a particular toll on the young, and has been linked to high rates of youthful criminal behavior, injury, and impaired ability to achieve educational qualifications. Many deaths and much disease and suffering could be prevented by reducing alcohol use and related problems. The most effective approach to reduce alcohol-related problems is to implement a comprehensive set of measures to reduce alcohol consumption and related problems. Policy options include price increases, restrictions on availability, strong drink-driving legislation and ready access to treatment. Some countries have succeeded in reducing per capita consumption substantially, and consequently have reduced liver cirrhosis deaths, a common indicator of alcohol-related problems in a society. Efforts to reduce alcohol consumption and related problems face formidable obstacles: alcohol dependence; social pressures; aggressive alcohol marketing and promotion; other pressing health problems competing for limited resources. The overall trend is towards stricter laws and increased enforcement in some areas such as drinking-driving. Provision of treatment for drinking problems has increased in many places in recent decades.